If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + 7 + -5x = -6 Reorder the terms: 7 + 6x + -5x = -6 Combine like terms: 6x + -5x = 1x 7 + 1x = -6 Solving 7 + 1x = -6 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + 1x = -6 + -7 Combine like terms: 7 + -7 = 0 0 + 1x = -6 + -7 1x = -6 + -7 Combine like terms: -6 + -7 = -13 1x = -13 Divide each side by '1'. x = -13 Simplifying x = -13
| 7a+15+a=55 | | 15x+8+12=7x+4 | | 12x+9y=qt | | 1x+4-15=2 | | (6x+8)-(3x+1)=22 | | N+(n+5)=25 | | [6-3x]=3 | | 12x=15x-6 | | 4n^2-10n+18=9 | | 5h+64=-76 | | C=3.14*2*7.2 | | 4n-48=12 | | 2=3(14)+x | | -2x=y+3 | | T/9=-7 | | 5ln(x+7)-6lnx= | | 2d-10-5d=47 | | 6=8(s-3/4-20) | | 9(5y-8)= | | 17-7/2x=1 | | 196=24-w | | b^2+46-12=0 | | 144k^2+24k+1=0 | | 3x+7=5x+2 | | Z-8=4z | | 18i-2g=4g | | 2y+4-1y=16 | | 2x^2+26x-13=0 | | 8-2x=-12(x+7) | | 2x/y | | 4x-4=-14 | | 3(2x-3)=4x-9 |